2022
DOI: 10.24059/olj.v26i1.2607
|View full text |Cite
|
Sign up to set email alerts
|

“Simplicity is Key”: Literacy Graduate Students’ Perceptions of Online Learning

Abstract: Even before COVID-19, literacy graduate coursework was increasingly offered online, replacing the traditional campus-based courses This study investigated how graduate literacy students perceive coursework in an online learning environment. This understanding is important because (a) student perceptions regarding online learning are critical to motivation and learning; and (b) faculty designing courses need to consider student voice in course development. This survey research queried literacy master’s degree c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Bali and Liu [35] also achieved similar results, as students preferred traditional lectures, but they quickly discovered the potential and positive side of online education (autonomy, time-saving, cost-effectiveness). Van et al [36] found that online education was positively judged by students. Therefore, they suggest that teacher training colleges should specialize in preparing trainers online, allowing for the opportunity to continue online lectures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bali and Liu [35] also achieved similar results, as students preferred traditional lectures, but they quickly discovered the potential and positive side of online education (autonomy, time-saving, cost-effectiveness). Van et al [36] found that online education was positively judged by students. Therefore, they suggest that teacher training colleges should specialize in preparing trainers online, allowing for the opportunity to continue online lectures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the outbreak of Covid-19, studies on students’ perception of emergency online teaching and their adaptation to blended learning when the virus turned into a “new normal” accumulated. Across the globe, many studies reported students’ positive experience of studying online, for example, Almahasees et al (2021) in Jordan, Van Wig et al (2022) in the US, Poláková and Klímová (2021) in Slovakia, and the aforementioned Macau based studies (e.g., Gong et al, 2021; Guan et al, 2023; Hsiang et al, 2022). Meanwhile, there is a large amount of research revealed that students’ online learning experiences were unsatisfactory due to the following reasons: students’ loyalty to offline education (Blizak et al, 2020), inadequate digital access, unsuitable home learning environment, and shortage of necessary computer skills (Cranfield et al, 2021), students’ anxiety in the pandemic (Howcroft & Mercer, 2022), fatigue and demotivation after constant virtual learning (Zizka & Probst, 2023), the inability to obtain timely feedback and to achieve in online learning (Conrad et al, 2022; Warfvinge et al, 2022), the shortage of socialization in online learning (Siah et al, 2022), not being self-regulated learners (Yeung & Yau, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students in higher education choose online learning because of its flexibility, convenience, and accessibility (Alsayed & Althaqafi, 2022;Harris & Martin, 2012). Students' perceptions of learning are influenced by students' attitudes and their digital literacy skills (Prior et al, 2016;Van Wig et al, 2022). With the spread of distance education, the lack of social relations between individuals increases in distance education and this indicates that the demand for building interactive relationships between students and teachers increases (Amemado & Manca, 2017;Sun & Chen, 2016).…”
Section: Introductionmentioning
confidence: 99%